The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/infrastructures2040014
|View full text |Cite
|
Sign up to set email alerts
|

Creating Stakeholder Value through Risk Mitigation Measures in the Context of Disaster Management

Abstract: Abstract:The resilience of critical infrastructure (CI) to extreme weather events (EWE) is one of the most demanding challenges for all stakeholders in modern society. Although partial risk reduction is feasible through the introduction and implementation of various risk mitigation measures (RMM), decision-makers at all decision-making levels are pressured to find ways to cope with the impending extreme weather and to have a thorough understanding of the EWE impacts on CI. This paper discusses how the value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…33 These indicators for “COVID-19 Mitigation” were characterized by risk mitigations in the context of disasters (proportionate, adequate, self-containment, global impact) and were modified as self-reported questions. 34 Examples: “I feel relief with the degree of technology measures on COVID-19,” “enough efforts rendered on fighting the pandemic,” “I agree to some good policies applied during the pandemic,” “there are available possibilities to contain the virus,” and “the community compliance measures for the pandemic.” With items scored using 5-point Likert scale from strongly disagree 1 to strongly agree 5 aimed to assess COVID-19 risk mitigation (outcome variable) based on the technology of health apps.…”
Section: Methods and Measurementsmentioning
confidence: 99%
“…33 These indicators for “COVID-19 Mitigation” were characterized by risk mitigations in the context of disasters (proportionate, adequate, self-containment, global impact) and were modified as self-reported questions. 34 Examples: “I feel relief with the degree of technology measures on COVID-19,” “enough efforts rendered on fighting the pandemic,” “I agree to some good policies applied during the pandemic,” “there are available possibilities to contain the virus,” and “the community compliance measures for the pandemic.” With items scored using 5-point Likert scale from strongly disagree 1 to strongly agree 5 aimed to assess COVID-19 risk mitigation (outcome variable) based on the technology of health apps.…”
Section: Methods and Measurementsmentioning
confidence: 99%
“…Based on the INTACT project co-founded by the European Union, Räikkönen et al ( 2017 ) focus on Risk Management Measures (RMM). In particular, the study contributes to the value creation of RMM, which is crucial for decision-making and for the development of strategies to prevent or reduce the impacts of extreme weather events.…”
Section: Descriptive Findingsmentioning
confidence: 99%
“…Most infrastructures, due to long life cycles that extend decades into the future, will be more and more likely to experience vulnerabilities due to climate change, which is expected to increase the magnitude and frequency of extreme events such as heatwaves, forest fires, floods, violent storms, and strong winds. Risk management for uncertain events caused by climate change and strengthening the resilience of infrastructure systems are high priorities for technical experts and scholars (Balston et al, 2017;Räikkönen et al, 2017) and of interest to governments and the EU (e.g., US Department of Homeland Security, 2012; Karagiannis et al, 2019) and the Intergovernmental Panel on Climate Change (IPCC, 2018). The IPCC (2018) has anticipated the infrastructural impacts of extreme weather events to be manifold.…”
Section: Climate Changementioning
confidence: 99%
“…In all Nordic countries, remote areas have historically suffered from a high frequency of lengthy electrical power failures because of the vulnerability of overhead power lines to weather events, especially windstorms, which has created an active political debate over protecting these infrastructures (Heidenstrøm & Throne-Holst, 2020;Räikkönen et al, 2017;Rinkinen, 2013;Silvast, 2017). Examining extreme winter events and electricity distribution in Finland, one study concluded that relevant risk mitigation should not only be valued in monetary terms and investment analyses (cf.…”
Section: Infrastructures and Vulnerabilities Caused By Climate Change In The Nordic Countriesmentioning
confidence: 99%
See 1 more Smart Citation